Anxiolytic effects of fluoxetine and nicotine exposure on exploratory behavior in zebrafish - Matthew L. Singer; Kris Oreschak; Zachariah Rhinehart; Barrie D. Robison (PeerJ, 2016)
Zebrafish (Danio rerio) have emerged as a popular model for studying the pharmacology and behavior of anxiety. While there have been numerous studies documenting the anxiolytic and anxiogenic effects of common drugs in zebrafish, many do not report or test for behavioral differences between the sexes. Previous studies have indicated that males and females differ in their baseline level of anxiety. In this study, we test for a sex interaction with fluoxetine and nicotine. We exposed fish to system water (control), 10 mg/L fluoxetine, or 1 mg/L nicotine for three minutes prior to being subjected to four minutes in an open-field drop test. Video recordings were tracked using ProAnalyst. Fish from both drug treatments reduced swimming speed, increased vertical position, and increased use of the top half of the open field when compared with the control, though fluoxetine had a larger effect on depth related behaviors while nicotine mostly affected swimming speed. A significant sex effect was observed where females swam at a slower and more constant speed than males, however neither drug produced a sex-dependent response.